Analisis Dan Identifikasi Implementasi Sistem Informasi Manajemen Keuangan (Studi Kasus Pada Pt. Pojur) - Asadi Khas (JAF (Journal of Accounting and Finance), 2023)
This study aims to analyze and identify the implementation of the Financial Management Information System (SIMK) at PT. Pojur. The research was conducted using qualitative methods and case studies as a research approach. Data were obtained through in-depth interviews with SIMK users at PT. Pojur and analysis of documents related to the use of SIMK in companies. The results showed that the implementation of SIMK at PT. Pojur has had a positive impact on the company's financial management. SIMK has helped improve the efficiency and effectiveness of the company's financial management to improve the company's overall performance. In addition, SIMK has also facilitated the monitoring of the use of company funds and increased the transparency of corporate financial reporting. However, this study also found several obstacles encountered in implementing SIMK at PT. Pojur. These obstacles include the lack of support and maximum use from the company's management and the lack of understanding and training on the use of SIMK from users. In conclusion, this study shows the implementation of SIMK at PT. Pojur has had a positive impact on the company's financial management. However, efforts need to be made to overcome the obstacles faced so that the use of SIMK can be optimal and provide greater benefits for the company. Keywords: Analysis, Identification, SIMK